Seroprevalence and factors associated with Toxoplasma Gondii, Neospora caninum, and Besnoitia besnoiti infections in cattle and goats in Selangor, Malaysia - Sadiq, Mohammed Babatunde; Muhamad, Azim Salahuddin; Hamdan, Siti Aisyah; Ramanoon, Siti Zubaidah; Zakaria, Zunita; Abdul Aziz, Nor Azlina; Mansor, Rozaihan; Arshad, Siti Suri; Khalid, Nurulhidayah; Abdul Hamid, Norhamizah; Kamaludeen, Juriah; Syed-Hussain, Sharifah Salmah (Multidisciplinary Digital Publishing Institute, 2022)
Apicomplexan parasites such as Toxoplasma gondii, Neospora caninum, and Besnoitia besnoiti are widely recognized as causes of production diseases in ruminants. This study aimed to investigate the serological occurrence of T. gondii, N. caninum, and B. besnoiti in cattle and goats from smallholder farms in Selangor, Malaysia. A cross-sectional study was conducted on 19 farms by collecting 404 bovine (n = 225) and caprine (n = 179) serum samples, which were then essayed for T. gondii, N. caninum, and B. besnoiti antibodies using commercially available ELISA test kits. Farm data and animal characteristics were documented, and the data were analyzed using descriptive statistics and logistic regression models. The seroprevalence of T. gondii at animal and farm levels in cattle was 5.3% (95% CI 1.2-7.4%) and 36.8% (95% CI 22.4-58.0%), respectively. Animal-level seropositivity for N. caninum was 2.7% (95% CI 0.4-4.2%) and 5.7% for B. besnoiti (95% CI 1.3-9.4%) with corresponding farm-level seropositivity of 21.0% and 31.5%, respectively. For the goat samples, a high animal- (69.8%; 95% CI 34.1-82.0%) and farm-level (92.3%) seropositivity was recorded for T. gondii, but was relatively lower for N. caninum antibodies, at 3.9% (95% CI 1.5-6.2%) and 38.4% (5/13). The factors associated with T. gondii seropositivity were older animals (above 12 months) (OR = 5.3; 95% CI 1.7-16.6), semi-intensive farms (OR = 2.2; 95% CI 1.3-6.2), the presence of either dogs or cats (OR = 3.6; 95% CI 1.1-12.3), a large herd size (>100 animals) (OR = 3.7; 95% CI 1.4-10.0), and a single source of replacement animals (OR = 3.9; 95% CI 1.6-9.6). These findings are vital in developing effective control measures against these parasites in ruminant farms in Selangor, Malaysia. More national epidemiological research is required to elucidate the spatial distribution of these infections and their potential impact on Malaysia's livestock industry.